2010
DOI: 10.1063/1.3426084
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of soft x-ray amplifiers by controlling plasma hydrodynamics

Abstract: Abstract. Several coherent soft x-ray lasers are available for applications nowadays. Among them, plasma-based soft x-ray lasers promise to genérate high-energy, highly coherent, short pulse beam. Solid target based amplifiers, due to the fact that his density is higher, should store a higher amount of energy. However, to-date output energy from seeded solid amplifiers remains as low as 60 nJ. We demonstrated that the extraction of the energy stored in the plasma is enhanced by carefully tailoring the plasma s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…In this letter we have shown how to construct an infinite class of higher derivative gravity theories. Notice that somewhat similar theories to the ones constructed here have appeared recently in the literature, but in higher dimensions [11][12][13][14]. By imposing suitable constraints on the parameters of the lagrangian we have found that it is possible to define a holographic version of the c-theorem, and that the central charge so obtained is consistent with a calculation of entropy in a black hole background.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In this letter we have shown how to construct an infinite class of higher derivative gravity theories. Notice that somewhat similar theories to the ones constructed here have appeared recently in the literature, but in higher dimensions [11][12][13][14]. By imposing suitable constraints on the parameters of the lagrangian we have found that it is possible to define a holographic version of the c-theorem, and that the central charge so obtained is consistent with a calculation of entropy in a black hole background.…”
Section: Discussionsupporting
confidence: 76%
“…Therefore in computing the entropy only invariants of the form R p contribute. Using that R = −6f ∞ /L 2 , the lagrangian must necessarily be of the same form as (14) with…”
Section: Black Hole Solutions and Entropymentioning
confidence: 99%
“…Considering the same action in dimensions other than four, one loses the property of invariance under Weyl rescalings. Even then, the theory admits exact analytic black hole solutions with spherical, planar or hyperbolic symmetry, and further admits Birkhoff's theorem [9]. Note that, in arbitrary dimensions, though the field equations are of fourth order, the trace of the field equations are of order two.…”
Section: Introductionmentioning
confidence: 99%